Performance analysis of terrestrial 6G networks in tropical region - Husam M. Banwair; Jafri Din; Khalid Ibrahim Alkhedhairi; Ahmed Basahel (Universitas Ahmad Dahlan, 2024)
Next-generation (NG) optical technologies are expected to offer high data rates, multiple broadband services, expandable bandwidth, and flexible communication options for diverse end users. In optical technologies, free space optical (FSO) technology stands out as a promising component to meet the requirements of terrestrial sixth generation (6G) networks. This is due to its cost-effectiveness, ease of deployment, high bandwidth capacity, and robust security features. However, haze and rain are major challenges to FSO link performance. These adverse weather conditions reduce visibility, causing significant attenuation of the laser signal. The resulting attenuation negatively impacts the performance and availability of the FSO link. This paper assesses the performance of a terrestrial FSO link under tropical climate conditions. Predicted attenuation due to haze is analyzed and compared using two wavelengths: 850 nm and 1550 nm. The predicted attenuation is based on a whole year of visibility data in Malaysia, from January 1, 2023 to December 31, 2023. Additionally, the availability of the two wavelengths is evaluated. The findings show that higher wavelengths experience lower attenuation compared to lower wavelengths. These results provide valuable insights into the feasibility of deploying FSO links in tropical climates.